Inequalities in living well with dementia—The impact of deprivation on well‐being, quality of life and life satisfaction: Results from the improving the experience of dementia and enhancing active life study. (8th October 2018) - Wu, Yu‐Tzu; Clare, Linda; Jones, Ian Rees; Martyr, Anthony; Nelis, Sharon M.; Quinn, Catherine; Victor, Christina R.; Lamont, Ruth A.; Rippon, Isla; Matthews, Fiona E.; ,
Abstract : Objectives: Area level factors, such as deprivation and urban/rural settings, have been associated with variation in local resources and services and health inequality in later life. The aim of this study is to investigate the potential impact of deprivation and urban/rural areas on capability to live well with dementia and to examine whether availability of informal carers modified the associations. Methods: The analysis was based on a large cohort study of 1547 community‐dwelling people with dementia across Great Britain. Quality of life, life satisfaction, and well‐being were measured as indices of "living well." Multivariate modelling was used to investigate differences in living well measures across deprivation quintiles and urban/rural areas adjusting for sociodemographic factors and number of comorbidities and stratifying by three groups: those living with a carer, those with a noncoresident carer and those without a carer. Results: Negative dose‐response relationships between deprivation and measures of quality of life (−2.12; 95% CI: −3.52, −0.73), life satisfaction (−1.27; 95% CI: −2.70, 0.16), and well‐being (−5.24; 95% CI: −10.11, −0.36) were found in participants living with a carer. The associations were less clear in those with a noncoresident carer and those without a carer but these two groups generally reported lower scores on living well indicators than participants living with a carer. There was no urban/rural difference. Conclusions: The findings suggest inequalities in living well with dementia according to levels of deprivation. Additional resources are needed to improve postdiagnostic care in highly deprived areas and support those who have no informal carer.